Efeito de soluções ativadas por ultrassom na resistência adesiva de pinos de fibra de vidro cimentados com cimento resinoso autoadesivo - Barreto, Mirela Sangoi (2015)
The current study aimed to evaluate the effect of irrigating and chelating solutions on bond strength of fiber glass posts cemented with RelyX U200. 60 single-rooted premolars were sectioned at 14 mm from the apex, prepared with ProTaper Universal system until F3 instrument and filled with F3 master cone and AH Plus sealer. Root canal filling was partially removed, remaining 4 mm of guta-percha at the apical third. Specimens were randomly divided into 5 experimental groups (n=12), according to the solution used before fiber post cementation (dentin surface treatment), as described: EDTA 17% (EDTA); QMix (QM); SmearClear (SC); NaOCl 2.5% (NaOCl) and saline solution as control group (SS). Ultrasonic activation was performed three times, during 20 seconds each and root canals were dried with paper points. Exacto N2 glass fiber posts were cemented with RelyX U200. Rhodamine B dye was mixed to RelyX U200 in one specimen per group, in order to provide fluorescence for confocal laser scanning microscopy (CLSM) assessment. A cutting machine was used for root s sectioning, providing 3 slices, one for each root third. Next, push-out test was performed. Stereomicroscope and CLSM were used to analyze the failure mode and to illustrate the pattern of distribution of RelyX U200 inside dentinal tubules, respectively. Bond strength mean were calculated and ANOVA and Bonferroni tests were used for statistical analysis. SS showed the higher mean of bond strength values, superior to QM, SC (P < .05). NaOCl presented intermediary bond strength values, similar to EDTA and SS (P > .05). QM and SC showed the lowest mean of bond strength (P < .05). In conclusion, SS and NaOCl associated to ultrasonic activation seems to be adequate solutions for root canal cleaning before fiber post cementation with RelyX U200, while chelating solutions, such as EDTA, QMix and SmearClear, should not be used for dentin pre-treatment when cementing with RelyX U200.